The role of death technologies in grief: an interdisciplinary examination of AI, cognition, and human expression - Sri Takshara, K; Bhuvaneswari, G (Frontiers in Human Dynamics, 2025)
IntroductionIn an era where technology is increasingly mediating human experience, grief too is being reshaped. This study explores how emerging death technologies like AI-generated voicebots alter our understanding and processing of loss. Using the character of Dimple Ahuja from Mismatched Season 3 as a narrative lens, the paper examines the emotional and cognitive shifts that occur when individuals use artificial simulations such as the ‘Dadbot’ to stay connected with deceased loved ones.MethodThe study adopts a qualitative, phenomenological approach, analysing selected scenes and dialogues from Mismatched Season 3. The fictional narrative is treated as a cultural artefact that reflects real-world emotional dilemmas. A textual analysis is combined with insights from cognitive neuroscience, psychology, and ethics. The author’s autoethnographic reflections enrich the interpretation, grounding theoretical discussion in lived experience.ResultsFindings suggest that the ‘Dadbot’ offers temporary comfort by simulating presence, allowing Dimple to feel emotionally connected to her deceased father. However, it also risks fostering emotional dependency, delaying the acceptance of loss, and interfering with neurobiological healing processes such as neuroplasticity and emotional regulation. Psychologically, the simulation supports avoidance behaviors, while ethically, it challenges notions of memory authenticity and consent.DiscussionSimulated grief technologies present a complex duality: they provide solace but risk disrupting the natural mourning process. From a phenomenological perspective, tools like the ‘Dadbot’ blur the lines between presence and absence, reality and simulation. The study concludes that while AI can support grief navigation, its use must be ethically designed and emotionally grounded, ensuring that technological continuity does not replace the irreplaceable truth of loss and love.